Intermittent pair‐housing, pair relationship qualities, and HPA activity in adult female rhesus macaques - Hannibal, Darcy L.; Cassidy, Lauren C.; Vandeleest, Jessica; Semple, Stuart; Barnard, Allison; Chun, Katie; Winkler, Sasha; McCowan, Brenda (American journal of primatology, 2018)
Laboratory rhesus macaques are often housed in pairs and may be temporarily or permanently separated for research, health, or management reasons. While both long‐term social separations and introductions can stimulate a stress response that impacts inflammation and immune function, the effects of short‐term overnight separations and whether qualities of the pair relationship mediate these effects are unknown. In this study, we investigated the effects of overnight separations on the urinary cortisol concentration of 20 differentially paired adult female rhesus macaques (Macaca mulatta) at the California National Primate Research Center. These females were initially kept in either continuous (no overnight separation) or intermittent (with overnight separation) pair‐housing and then switched to the alternate pair‐housing condition part way through the study. Each study subject was observed for 5 weeks, during which we collected measures of affiliative, aggressive, anxious, abnormal, and activity‐state behaviors in both pair‐housing conditions. Additionally, up to three urine samples were collected from each subject per week and assayed for urinary free cortisol and creatinine. Lastly, the behavioral observer scored each pair on four relationship quality attributes (“Anxious,” “Tense,” “Well‐meshed,” and “Friendly”) using a seven‐point scale. Data were analyzed using a generalized linear model with gamma distribution and an information theoretic approach to determine the best model set. An interaction between the intermittent pairing condition and tense pair adjective rating was in the top three models of the best model set. Dominance and rates of affiliation were also important for explaining urinary cortisol variation. Our results suggest that to prevent significant changes in HPA‐axis activation in rhesus macaque females, which could have unintended effects on research outcomes, pairs with “Tense” relationships and overnight separations preventing tactile contact should be avoided. Overnight separations of tense pairs are associated with increased HPA‐axis activity. Continuous and compatible pair‐housing are recommended. When separating overnight, contact via bars or grates may improve welfare and alleviate unintended effects.